Field-induced ferroelectricity in paraelectric phase of Barium strontium titanate - Tomar V.; Jha P.A.; Jha P.K.; Singh P. (My University, 2025)
The nonlinear polarization and ferroelectricity in the paraelectric region of Ba0.7Sr0.3TiO3 ceramic samples are investigated. For this, samples are poled at a finite field and field-induced phase is analyzed through XRD, SEM, dielectric, impedance, and Piezo force microscopy high-frequency studies before and after poling. The Rayleigh-like dynamics is inspected along with the switching behavior in to samples. Our study suggests field-induced ferroelectricity in Ba0.7Sr0.3TiO3 due to polar distortion. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.